Reestablishing Brain Networks in Patients without Overt Hepatic Encephalopathy after Liver Transplantation. Issue 12 (December 2014) - Lin, Wei-Che; Hsu, Tun-Wei; Chen, Chao-Long; Lu, Cheng-Hsien; Chen, Hsiu-Ling; Cheng, Yu-Fan; Lin, Ching-Po
Cirrhotic patients without overt hepatic encephalopathy (HE) have associated with widespread neuro-psychological impairment. Liver transplantation can restore metabolic abnormalities but the mechanisms are unclear. We investigate brain functional networks after transplantation using resting-state funtional magnetic resonance imaging (MRI). Twenty-six cirrhotic patients without overt HE completed neuro-psychological assessment before and 6 to 12 months after transplantation, and compared with 35 healthy controls. Five major functional brain networks, default mode (DMN), dorsal attention (DAN), executive control (ECN), salience (SN), and primary networks (PN), were assessed. Nodal efficiency and strength in different functional networks were weighed and their interaction metrics displayed. Granger causal analysis between pretransplantation and posttransplantation was performed. Before transplantation, the intrafunctional connectivity was decreased in DMN, DAN, ECN, and SN. After transplantation, cognitive functions improved with increased functional connectivity. The interaction metrics among large-scale networks in patients became similar to healthy controls. The increase in PN affected the decrease in SN, while the increase in DAN forced a decrease in DMN. There was a bidirectional balance between DMN and SN. Dynamic disruptions and reconstruction in intrinsic large-scale networks are associated with parallel patterns of cognitive information processing deficits and recovery. Remapping of SN, DMN, and DAN is essential for restoring cognition after transplantation.